2009
DOI: 10.1002/pssa.200824228
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and microcrystalline GeC:H films prepared by magnetron sputtering

Abstract: Hydrogenated germanium‐carbon alloy (GeC:H) films have been deposited by a reactive rf magnetron sputtering of Ge in methane–argon gas mixtures. As the second sputtering gas, helium is utilized in order to control the film properties. The effect of helium partial pressure ratio R to the total sputtering gas on the structural, optical and electrical properties of the films was investigated. The films show the amorphous nature in the low‐R range up to 60%. In the high‐R range above 60%, the bonding configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The increase of Ge−C band intensity indicated that the concentration of the substitutional carbon could be controlled by CVD growth parameters. 54,55 The Ge (111) diffraction peak positions of Ge 1−x C x alloy NWs under different growth conditions were carefully evaluated in order to investigate structural change by carbon incorporation (Figure 4e, f). The lattice constant of the alloy NWs was calculated from the XRD pattern and Bragg equation (see Figure S2 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of Ge−C band intensity indicated that the concentration of the substitutional carbon could be controlled by CVD growth parameters. 54,55 The Ge (111) diffraction peak positions of Ge 1−x C x alloy NWs under different growth conditions were carefully evaluated in order to investigate structural change by carbon incorporation (Figure 4e, f). The lattice constant of the alloy NWs was calculated from the XRD pattern and Bragg equation (see Figure S2 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Two strong absorption bands around 590 and 640 cm –1 were clearly visible, and were attributed to the Ge–H wagging and Ge–C vibrations, respectively. As the growth temperature and partial pressure of carbon were increased, the intensity of the absorption band corresponding to the Ge–C stretching vibration was increased dramatically (Figure c, d). The increase of Ge–C band intensity indicated that the concentration of the substitutional carbon could be controlled by CVD growth parameters. , The Ge (111) diffraction peak positions of Ge 1– x C x alloy NWs under different growth conditions were carefully evaluated in order to investigate structural change by carbon incorporation (Figure e, f). The lattice constant of the alloy NWs was calculated from the XRD pattern and Bragg equation (see Figure S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Gazicki and Janowska reported that thin germanium/carbon alloy films prepared by radio frequency glow discharge using tetraethylgermanium . Since these early studies, Saito and Hu have produced films by reactive radio frequency magnetron sputtering of germanium in methane–argon gas mixtures. However, a great deal of hydrogen content from the precursors remained in the films.…”
Section: Introductionmentioning
confidence: 99%